The Integration of the “Breve declaración de las sentencias y vocablos obscuros” by Alejo Venegas in the "Tesoro" de Covarrubias and Other Lexicographic Repertoires of the 18th-20th centuries - Almansa Ibáñez, Soraya (2024)
The aim of this work is to analyze the impact of Alejo Venegas del Busto’s Breve declaración de las sentencias y vocablos obscuros in Covarrubias’ Thesaurus, as well as in different works of later centuries, where Venegas is considered as an etymological authority. This glossary is an annex to the work of Erasmist spirit the Agonía del tránsito de la muerte (1543) which, despite not having a dictionary approach, has contributed significantly to lexicographical praxis. A detailed search has been made of the accredited voices in Venegas’ glossary to know which of them have had the greatest influence on the work of Covarrubias. To complete the analysis, matching samples are provided in representative lexicographical works. The purpose is to deepen the knowledge of Venegas’ work to determine what his contribution to Covarrubias’ work was, as well as its influence on other lexicographic repertoires.